2022
DOI: 10.1111/joca.12452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceived scarcity on COVID‐19 consumer stimulus spending: The roles of ontological insecurity and mutability in predicting prosocial outcomes

Abstract: In 2021, the United States government provided a third economic impact payment (EIP) for those designated as experiencing greater need due to the COVID‐19 pandemic. With a particular focus on scarcity and ontological insecurity, we collected time‐separated data prior to, and following, the third EIP to examine how these variables shape consumer allocation of stimulus funds. We find that scarcity is positively associated with feelings of ontological insecurity, which, interestingly, correlates to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Additionally, this scarcity model shows that individuals respond to resource constraints through two different psychological approaches: by directly eliminating differences in resources and gaining control over other areas of their lives [ 14 ]. However, there has not been much research on the perceived mutability of the scarcity scenario [ 7 , 8 ]. The present study bridged this gap by adopting the mutability scales developed by Leary et al (2022) and adapting manipulation concerning perceived mutability [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this scarcity model shows that individuals respond to resource constraints through two different psychological approaches: by directly eliminating differences in resources and gaining control over other areas of their lives [ 14 ]. However, there has not been much research on the perceived mutability of the scarcity scenario [ 7 , 8 ]. The present study bridged this gap by adopting the mutability scales developed by Leary et al (2022) and adapting manipulation concerning perceived mutability [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, this is also mirrored with research into ontological insecurity. Several articles have been published in the aftermath of the Covid-19 pandemic, and whilst different sub-focuses are offered, they agree that ontological insecurity has also increased in this timeframe (see Wright et al, 2021 ; Agius et al, 2020 ; Leary et al, 2022 ; etc.). A correlation is no guarantee of a causal relationship, but the potential of this link strengthens with a refocussed application of ontological (in)security.…”
Section: Ontological (In)security Mental Illness and Societymentioning
confidence: 99%
“…We must consider the possibility that this pandemic is acting upon an existing ontologically insecure position, a position Giddens and many others would endorse (Wright et al, 2021 ; Agius et al, 2020 ; Leary et al, 2022 ). Even joining the dots outside of Giddens et al, with a year-on-year increasing incidence of mental illness diagnosis, based on data collated from 1993 onwards (Bastiampillai et al, 2019 ; ONS, 2021a ; NHSBSA, 2021 ), an existential argument can be presented that the ‘ordinary circumstances of living’ are already challenging our ‘threshold of security’.…”
Section: Pre-existing Ontological Insecuritymentioning
confidence: 99%
“… 18 Studies show that ontological security can predict the impact of changes in the social environment on personal security during a disease pandemic and that it has a beneficial early warning effect on people’s behavior trends in times of crisis. Yang et al 19 showed that the pandemic-induced scarcity perception of ontological security could promote migrant workers’ risk-taking tendency, while Leary et al 20 found that it could stimulate people’s consumption. However, there are few reports on inpatients’ level of ontological security and its impact on daily epidemic prevention behavior under the normalization of the current COVID-19 pandemic situation.…”
Section: Introductionmentioning
confidence: 99%